2006
DOI: 10.1080/13102818.2006.10817347
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Proteolytic Activity of Lactobacilli Isolated from Kefir Grains

Abstract: The proteolytic activity of 276 natural isolates from kefir grains was investigated. Evidence for extracellular proteolytic activity was demonstrated for 49 Lactobacillus strains. One strain, Lactobacillus kefir DR22x, was selected as a producer of proteinases. Lactobacillus kefir DR22x strain produces a cell-wall-bound proteinase. The proteinase was removed from the cell envelope by washing the cells with a Ca 2+-free buffer. The crude proteinase extract showed the highest activity at pH 7.2 and 37 ºC. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 12 publications
3
9
1
2
Order By: Relevance
“…In the current study, the optimum pH was pH 7.0 (Table 4) and decreased towards the acidity. These findings agreed with Fira, [39], Kabadjova-Hristova [33], and El-Ghaish et al [38], with some variations but with the same trend. The variations might be due to the difference in bacterial species.…”
Section: E Phsupporting
confidence: 82%
See 4 more Smart Citations
“…In the current study, the optimum pH was pH 7.0 (Table 4) and decreased towards the acidity. These findings agreed with Fira, [39], Kabadjova-Hristova [33], and El-Ghaish et al [38], with some variations but with the same trend. The variations might be due to the difference in bacterial species.…”
Section: E Phsupporting
confidence: 82%
“…Other literature elicited that the proteolytic activity increases with increase in incubation time till 36h of incubation then the proteolytic activity begins to decline [36] that disagree with the current study and the previous study by Tufail et al [35]. That difference may be owing to species difference or isolation origin as it was investigated by Kabadjova-Hristova et al [33]. Kabadjova-Hristova et al [33], have found that according to the literature of Pereira et al [37], the proteinases of L. curvatus and L. homohiochii showed maximum activity in the early exponential phase, that findings disagreed with their investigations and informed that the disagreement is owing to the origin of the strain used which was isolated from kefir grains that presented too complex media.…”
Section: Incubation Periodcontrasting
confidence: 57%
See 3 more Smart Citations